Indoor and outdoor concentration of PM10, PM2.5 and PM1 in residential building and evaluation of negative air ions (NAIs) in indoor PM removal. Issue 1 (1st January 2020) - Nadali, Azam; Arfaeinia, Hossein; Asadgol, Zahra; Fahiminia, Mohammad
ABSTRACT: The present work was conducted in a two-part study. In part I, the levels of indoor and outdoor PM10, PM2.5, and PM1 was measured using real time GRIMM dust monitors. In part II, the performance of NAIs method was investigated on reduction of indoor concentration of PM in these residential buildings for the first time. Hourly average concentration and standard deviation (SD) of PM10 in indoor and outdoor at residential buildings were 63.5 ± 27.4 and 90.1 ± 33.5 µg/m 3, respectively. Indoor and outdoor concentrations of PM2.5 in residential buildings were 39.4 ± 18.1 and 49.5 ± 18.2 µg/m 3 and for PM1 the concentrations were 4.3 ± 7.7 and 6.5 ± 10.1 µg/m 3, respectively. We estimated that nearly 71.47% of PM10, 79.86% of PM2.5 and of 61.25% of PM1 in indoor of residential buildings can be removed by negative air ions.